Catholic universities as counter-cultural to universities PLC. Issue 2 (3rd July 2019) - Sullivan, John
Abstract : In The Christian Academic in Higher Education [Sullivan, John. 2018. The Christian Academic in Higher Education: The Consecration of Learning . London: Palgrave Macmillan], I make an extended attempt to explore what difference it might make if the tasks of academics in contemporary universities were interpreted and responded to in the light of Christian faith. By focusing on the central theme of the consecration of learning in that book I aim to offer an alternative picture of a university to the one that increasingly seems to dominate the scene today. There is a danger that universities, under the pressure of being subject to a combination of market-forces, targets, intrusive managerialism, measurement and surveillance, league tables, fierce competition for research grants, insistent individualism and curriculum fragmentation, will lose their soul. The university that emerges from the accumulation of these pressures seems to be envisaged as a business, as a publicly limited company (PLC). This article seeks to indicate some important features of an alternative vision for the university, one that is counter-cultural. 1